THE EFFECT OF THE MEMORIZATION MODEL ON THE MEMORIZATION OF SHORT LETTERS OF TKIT BAITURRAHMAN KARAWANG STUDENTS - Mardhyah, Annisa Nur'Ismah; Nur, Tajuddin; Ulya, Neng (Universitas Islam Madura, 2025)
The background of this research is based on the importance of mastering the memorization of the Qur'an from an early age as the foundation of Islamic character education as well as stimulating the cognitive, affective, and spiritual development of children. The research method uses a quantitative approach with a pre-experimental design of the one-shot case study type. The research subjects were class B students who participated in learning with the application of the memorization model. Data analysis was carried out by simple linear regression to measure the contribution of free variables to bound variables, as well as Spearman correlation test to see the tightness of relationships between variables. The results of the study showed that the memorization model had a positive and significant effect on improving the memorization of short letters. The value of the correlation coefficient of 0.839 with a significance of 0.000 (<0.05) confirms the existence of a strong relationship. The magnitude of the influence of the learning model on memorization was shown by the R square value of 0.704, which means that 70.4% of the variation in memorization improvement was directly influenced by the application of the memorization model, while 29.6% was influenced by other factors outside the study. These findings reinforce empirical evidence that memorization strategies can be an effective approach in Qur'an learning in early childhood Islamic educational institutions. In addition, this study provides practical implications for teachers and institutional managers in choosing the right learning model to foster children's love for the Qur'an while improving the ability to memorize systematically.